1992
DOI: 10.1002/jbm.820261109
|View full text |Cite
|
Sign up to set email alerts
|

Storage and elimination of titanium, aluminum, and vanadium salts, in vivo

Abstract: Hamsters were injected with titanium, aluminum, and vanadium salts either intraperitoneally or intramuscularly to study the transport, storage, and elimination of these metals. Blood samples were taken at 4 h or 24 h, and urine samples were taken at 24, 48, and 72 h. The hamsters were then injected weekly for 5 weeks after the initial injection. Blood and portions of the kidneys, liver, lung, and spleen were taken at sacrifice. All samples were analyzed for titanium, aluminum, and vanadium concentrations using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…These findings are consistent with the findings by Cruz et al (1995) demonstrating that daily administration of 500 [ig of orthovanadate for 10 days inhibited MDAY-D2 tumour growth in mice by over 85%. Interestingly, the in vitro drug-release profiles showed that paste containing 25% and 30% BMOV released approximately 500 [ig of BMOV per day, which is a similar daily dosage to that used previously (Cruz et al, 1995 Following intraperitoneal injections, the plasma levels of vanadate increase to very high levels almost immediately followed by a rapid clearance into the urine, as has been described previously (Harris et al, 1984;Merritt et al, 1992). Subcutaneous administration is likely to lead to high plasma concentrations within the first few hours of treatment followed by a rapid clearance.…”
Section: Discussionsupporting
confidence: 76%
“…These findings are consistent with the findings by Cruz et al (1995) demonstrating that daily administration of 500 [ig of orthovanadate for 10 days inhibited MDAY-D2 tumour growth in mice by over 85%. Interestingly, the in vitro drug-release profiles showed that paste containing 25% and 30% BMOV released approximately 500 [ig of BMOV per day, which is a similar daily dosage to that used previously (Cruz et al, 1995 Following intraperitoneal injections, the plasma levels of vanadate increase to very high levels almost immediately followed by a rapid clearance into the urine, as has been described previously (Harris et al, 1984;Merritt et al, 1992). Subcutaneous administration is likely to lead to high plasma concentrations within the first few hours of treatment followed by a rapid clearance.…”
Section: Discussionsupporting
confidence: 76%
“…Ni elimination occurs through urine and bile (Ishihara et al, 1991;Srivastava et al, 1990). The greatly elevated excretion of Ti through bile may be attributed to its accumulation in the liver, and according to Merritt and coworkers, Ti is not excreted through the urine (Merritt, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The contribution of elements released from dental restorations to the systemic body burden remains controversial, but the retention of artificially injected elements in various tissues demonstrates that released elements may accumulate in tissues over time. [9][10][11] The use of Ni-based alloys for dental restorations is a continuing concern because these alloys release levels of Ni which can approach daily dietary intake. 1 The corrosion of Ni-based dental alloys has been well documented in vitro [12][13][14] and in vivo, [15][16][17] particularly if the pH of the corroding solution falls below 6.0, 18 a common condition in the mouth.…”
Section: Introductionmentioning
confidence: 99%